Synthesis of K3[Fe(CN)6]-modified titanium dioxide photocatalyst and its application on the visible light photocatalytic degradation of acetaminophen - Gotostos, Mary Jane N. (2013)
Acetaminophen (ACT) is one of the most common and heavily used pharmaceutical and personal care products (PPCP?s) around the world and has been one of the most frequently detected PPCP?s in bodies of water, sewage treatment plant effluents , receiving surface water, and drinking water. The effects of dopant concentration, calcinations temperature, and calcinations time on the characteristics and photocatalytic activity K₃[Fe(CN)₆]/TiO₂ photocatalyst synthesized via sol-gel method were investigated. Characterizations were done using scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier Transform-Infrared (FTIR) spectroscopy, and Ultraviolet-Visible light diffuse reflectance spectroscopy (UV-Vis DRS). ACT was used for the photocatalytic activity test, done by degrading 0.1 mM initial ACT concentration in a 500-mL capacity batch reactor irradiated with five blue light emitting diodes (LED?s) for 9 h at 1 g/L photocatalyst ;loading, initial pH 6.9, 30˚C, and 400 rpm mixing. Optimum synthesis conditions were found to be at dopant concentration of 0.2 mL of 0.2 M K₃[Fe(CN)₆], 300˚C calcinations temperature, and 2 hrs calcinations time. K₃[Fe(CN)₆]/TiO₂ synthesized under these conditions have 4.88 times faster apparent degradation rate and 1.79 times higher amount of ACT degraded that commercially available Degussa P25 (DP25). The effects of initial pH, initial ACT concentration, photocatalyst dosage, system temperature, visible light wavelength, and number of light source on the photocatalytic degradation of ACT in a batch system were also investigated. Box-Behnken experimental design was employed to quantify the individual and interaction effects of initial pH, initial ACT concentration, and photocatalyst dosage at pre-determined ranges and optimize the response variable % ACT removed and kapp. At optimum conditions of 0.1 g/L photocatalyst dosage, 0.1 mM initial ACT concentration, and initial pH of 6.94, 91.06% ACT was removed after 9 h of irradiation with kapp = 3.97 x 10⁻³ min⁻¹. This work has successfully demonstrated the synthesis of a novel K₃[Fe(CN)₆]/TiO₂ photocatalyst using a simple sol-gel method for the effective visible-light photocatalytic degradation of ACT into less biologically toxic substances.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman
Keywords: Acetaminophen; Photocodes